Accounting Profits: An Institution - Bornemann, Alfred (Journal of Political Economy, 1943)
In this article the author presents accounting profits as an institution. According to the author the numerical estimates of profit become a business necessity with the expansion of the market and a corresponding increase in uncertainty. Such estimates are provided by accounting which attempts a quantitative clarification of the results of the utilization of productive forces. From the relatively simple record-keeping of an earlier period there have emerged the now highly complex, specialized functions of purchasing and marketing. Increasing problems also give rise to the expansion of interests concerned with personnel, managerial techniques, publicity, and other features. With the passage of time, increasing accounting requirements and techniques have been accompanied by the development of a body of highly involved doctrine. Public control is a further factor contributing to this result. Meanwhile, there is an ever-growing attempt on the part of accountants to arrive at a body of principles or standards which can be generally accented. In these tendencies the place of accounting profits as an institution manifests itself.